In-vivo deformation measurements of the human heart by 3D Digital Image Correlation. Issue 10 (16th July 2015) - Hokka, Mikko; Mirow, Nikolas; Nagel, Horst; Irqsusi, Marc; Vogt, Sebastian; Kuokkala, Veli-Tapani
Abstract Fast and accurate measurements of the kinetics and deformation of the heart during cardiac surgery can be useful for assessing the best strategies for the protection of the myocardium. While measurements based on ultrasonic technology such as the transesophageal echocardiography are rapidly developing in this direction, also other analysis methods based on optical imaging have been developed within the recent decade. The improved quality of digital cameras and increased computational power of personal computers have led to the development of deformation analysis method known as Digital Image Correlation (DIC). This paper presents preliminary results on the application of the DIC technique on analysing of the movement and deformation of the myocardial movement during a cardiopulmonary bypass surgery. The results show that the natural pattern of the heart should be sufficient for DIC, but better and more accurate results could be obtained with improved contrast conditions. DIC has a potential to be used as a sensitive tool for the surgeon to monitor the cardiac function.